Factors influencing marine ecological environment governance toward sustainability: a case study of Zhejiang Province - Chen, Linlin; He, Yuejun; He, Yuze (Frontiers in Marine Science, 2024)
At present, the marine ecological environment is facing enormous pressure from human activities, and there is an urgent need for coordinated governance by multiple entities to ensure that the marine ecological environment can continuously meet the needs of sustainable development. Marine ecological environmental governance plays multiple roles in the sustainable development of the ocean characteristics. Most existing studies have explored this field from the perspective of the government and public, while failing to adequately account for the factors influencing enterprises' participation in marine ecological environmental governance. This paper is an effort to provide some empirical research on the influencing factors of enterprises' participation in marine ecological environmental governance. Based on existing literature, empirical research (213 middle managers were surveyed from 68 coastal enterprises in Zhejiang, China) , this study extracts eight core factors that influence corporate participation in marine ecosystems and uses the Fuzzy Decision-making Trial and Evaluation Laboratory approach (Fuzzy DEMATEL). Furthermore, experts from Chinese backgrounds elucidated the complex interdependencies among the factors, based on which key influencing factors were identified. The empirical results indicate that government attention and support, legal and regulatory requirements, and cost-benefit accounting have a positive net effect on corporate participation in marine ecosystem management; when these factors are improved, they drive improvements in other factors(Corporate Capital Capability, Corporate Social Responsibility, Government Enforcement and Appraisal, The Attention of Corporate Leaders, Corporate Internal Management System). Additionally, interviews with Chinese business people support the robustness of the findings and suggest that policymakers cannot ignore government enforcement and assessment efforts. Overall, the study findings can help advance corporate participation in marine environmental governance. KEYWAORD sustainable development, corporate involvement, marine ecosystem, influencing factors, decision-making 字体: (默认)Palatino Linotype, (中文)